The Role of Critical Thinking Skills in Enhancing Students' Concept Mastery Through Innovative Learning Strategies: A Systematic Literature Review - Dewa Dwi Pranahita; Ni Ketut Anggriani; Nanda Aulia Pratiwi; Paramita Putri Apriyani; Sintya Dewi Lestari (Indonesian Journal of Applied Science and Technology, 2026)
The demands of 21st-century education require students to possess higher-order thinking skills (HOTS) to deeply and critically understand concepts in facing the complexities of the modern world. This study aims to systematically review the relationship between critical thinking skills and students’ concept mastery through a systematic literature review (SLR). The method involved selecting and analyzing ten relevant journal articles published within the last ten years. The findings indicate that critical thinking skills play a significant role in enhancing students’ concept mastery. Furthermore, innovative learning strategies such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), Concept Mapping, and Virtual Laboratory were consistently found effective in developing both variables. These strategies improve students’ abilities in analysis, synthesis, and evaluation, thereby strengthening comprehensive conceptual understanding. This review provides important implications for educators and curriculum developers to integrate learning approaches that stimulate critical thinking skills to achieve optimal concept mastery in the context of 21st-century education.